Teacher Efforts in Increasing Student Interest in Reading the Quran - Yemmardotillah, M; Hafizh, Muhammad; Faiz, Muhammad; Hamdi, Hafizul (STIT Ahlussunnah Bukittinggi, 2022)
This research uses descriptive qualitative methods. Data was collected through observation, interviews, and documentation. The data analysis uses the following steps, namely data reduction, data display, and drawing conclusions. The results of the analysis show the condition of interest in reading the Al-Quran of class VII students at the Legusa Community Learning Activity Center, Luak District, Lima Puluh Kota. Fifty Cities showed results that students' interest in reading the Quran was still low. The efforts carried out by Islamic Religious Education teachers are quite diverse. Starting from motivating students to be enthusiastic and happy when studying the Quran. Gives an overview of the virtues of reading the Quran. Give rewards to students who are serious about studying. Tadarus at the beginning of learning. Factors that influence Islamic Religious Education teachers in increasing interest in reading the Quran are factors within students, namely physiological and psychological factors in children. Factors from outside the student, the student's family, and their environment. lack of available lesson hours. This can be seen in students who do not repeat lessons at home. Because most of them have jobs while studying. Apart from that, there is also a lack of support from the family for them to study. So they really need to continue to be motivated and encouraged to be enthusiastic about learning.